(untitled) (Journal of Computational Mathematics, 1992)
With the help of Brouwer's fixed point theorem and the relations of the eigenvalues and diagonal elements of a Hermitian matrix, we give some new sufficient conditions for the solubility of algebraic inverse eigenvalue problems.